If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(n+3)+24=-4n-12
We move all terms to the left:
-7(n+3)+24-(-4n-12)=0
We multiply parentheses
-7n-(-4n-12)-21+24=0
We get rid of parentheses
-7n+4n+12-21+24=0
We add all the numbers together, and all the variables
-3n+15=0
We move all terms containing n to the left, all other terms to the right
-3n=-15
n=-15/-3
n=+5
| 0.5t=-10 | | 4y-13-2y+8=0 | | 5x-2=2(x+5) | | 3b2-7=68 | | (1/3)x+11=20 | | 24/15=n/5 | | 4x+73=2x+5 | | (3y-7)=y+7 | | (3x+20)=5 | | (8y+2)=(6y+12) | | 8(x+1)+5(x+7)=3 | | 5(4a+5)=9a+2 | | 9(k+5)=7k+6 | | 8n+(5n-9)=14 | | -4/3(w)=-8 | | 2v-3=11+12 | | -24=3(w-7)-6w | | a+6=22-7 | | 42x+19=25 | | Q=3000000x(1-0.02) | | 2•x=36 | | x+15=4x+10 | | 12+2x=8x-3 | | (4)(19)=x | | -2.5b+b=45 | | x=14/2/3 | | 6p2-12=5p | | 61p2-12=5p | | k+8=-13 | | C=7p+5=89 | | 5t+8=t+12 | | 5y^2-23-10=0 |